Spatiotemporal kinematics during top speed sprinting in male intercollegiate track and field and team sport athletes - Meng, C. R.; Walts, C. T.; Ryan, L. J.; Stearne, D. J.; Clark, K. P. (Sports Biomechanics, 2024)
We investigated spatiotemporal kinematics during top speed sprinting and biomechanical running strategies in 98 male intercollegiate athletes from a range of athletic backgrounds in track and field (TF, n = 28) and team sports (TS, n = 70). Participants completed 40 m running trials with sagittal plane motion analyses of high-speed video captured from 30 m to 40 m. Across the entire sample, measures of contact time, step rate, step length, flight length and duty factor (ratio of contact duration to stride duration) were meaningfully correlated with top speed (p < 0.05, 0.51 = |r or p| = 0.78). Flight time and contact length were weakly correlated with top speed (p < 0.05, 0.27 = |r or p| = 0.34). When comparing sub-groups of Slow TF (n = 14) and Fast TS athletes (n = 22) with similar top speeds (~9.3 m/s), Fast TS athletes clearly demonstrated a more ground-based strategy, with longer ground contact times and contact lengths, shorter flight times and flight lengths, and larger duty factors. Therefore, the results of this study suggest that existing technical models and normative metrics based on data from TF athletes could require modification when evaluating and coaching sprinting performance with TS athletes.